A new approach to prepare highly active and stable black titania for visible light-assisted hydrogen production. Issue 12 (21st October 2015) - Sinhamahapatra, Apurba; Jeon, Jong-Pil; Yu, Jong-Sung
Abstract : A highly active nano black TiO2 photocatalyst with Pt as a co-catalyst for visible light-assisted hydrogen production from methanol–water is prepared by controlled magnesiothermic treatment in a H2 /Ar atmosphere. Abstract : In spite of their remarkable enhancement in visible light absorption, black TiO2 materials have failed to demonstrate expected photocatalytic activity in visible light due to the presence of a high number of recombination centers. In this report, a new controlled magnesiothermic reduction has been developed to synthesize reduced black TiO2 under a 5% H2 /Ar atmosphere. The material possesses an optimum band gap and band position, oxygen vacancies, surface defects, and charge recombination centers and shows significantly improved optical absorption in the visible and infrared region. The synergistic effects enable the black TiO2 material to show an excellent hydrogen production ability in the methanol–water system in the presence of Pt as a co-catalyst. The maximum hydrogen production rates are 43 mmol h −1 g −1 and 440 μmol h −1 g −1, along with remarkable stability under the full solar wavelength range of light and visible light, respectively, and these values are superior to those of previously reported black TiO2 materials.